SATU DASAWARSA KOLABORASI ILMIAH RISET KESEHATAN ZONA INDONESIA - Himawanto, Himawanto (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2017)
Since health issues in Indonesia are seen as a common problem, scientific collaboration is growing and continuous. To examine collaboration indicators, study used bibliometric method based on research products published in ScienceDirect journal 2006-2015. The aims of this study are to detect level, index, sketch, and collaboration growth, including collaborators of national researchers. The results show that collaboration to overcome national health problems received high attention or 90% of the 146 generated research. Other collaboration levels exceeding limits of balance even though the research products, researchers, institutions, and countries often experience reduced growth. From number of research collaborations, Indonesia handles the largest number (63, 47.73%) and majority of them are multi-state. This best achievement is not separated on role of 40 national institutions and four of them highlighted the college and government. The geography is mostly located on the island of Java and the collaboration built in national institutions is also assisted by 28 countries. Collaborators are generally Asian and familiar to national institutions. National researchers should continue to raise health issues as cooperative baits with collaborators. So the goal to overcome the case and add international health publications can be realized.